Mathematical communication ability of students viewed from self-efficacy - A Aprisal; A M Abadi (International Conference on Mathematics and Science Education of Universitas Pendidikan Indonesia, 2018)
This research aimed to describe mathematical communication ability of students viewed from self-efficacy. This research was descriptive qualitative research. Subjects in this research were students of eight grade SMP Negeri 1 Marioriawa Kabupaten Soppeng Sulawesi Selatan. The data were collected by a test, questionnaire, and interview. Data analysis techniques consisted of three steps, namely: data reduction, data display, and make conclusion. The result of data analysis showed that students with high self-efficacy could master all indicators of mathematical communication ability, namely: ability to identify and write information needed in solving problems by using notation, symbol, or mathematical term; ability to translate the essay or word problems into the picture or sketch and create mathematics models; ability to use precise mathematics concepts in solving the problem. Students with moderate self-efficacy could master two indicators, namely: ability to identify and write information needed in solving problem by using notation, symbol, or mathematical term; ability to translate the essay or word problem into the picture or sketch and create mathematics model. Students with low self-efficacy were only able to master indicator of ability to identify and write the information needed in solving problem by using notation, symbol, or mathematical term.